“Tenho muito para contar, dizer que aprendi”: o ensino de história através da Olimpíada Nacional em História do Brasil (ONHB) e da Olimpíada de Ciências Humanas do Estado do Ceará (OCHE) - práticas docentes e aprendizagem histórica (2018 a 2022) - Araújo, Marisnanda Mota (2023)
This research is listed in the field of the Didactics of History and aims to investigate the teaching of history and the historical learning of students of Basic Education through their experiences in the National Olympiad in History of Brazil (ONHB) and in the Olympiad of Human Sciences of the State of Ceará (OCHE), between the years 2018 and 2022, period in which I participated in these competitions. The starting point of this research is the "writing of the self". This research also intends to discuss my experience as a teacher and to what extent my participation as a mentor teacher of teams in the aforementioned Olympiads, caused changes in the way I teach history. Therefore, the central hypothesis of this work is to analyze how the ONHB and the OCHE contribute to a significant students’ learning, aiming at the construction of the Historical Consciousness and what are the implications in my teaching practices along these five years of Olympic experience. To achieve this goal, we based our studies on Isabel Barca, Cristina Meneguello, Ridson Miranda, Jörn Rüsen among others. The methodology adopted was documental analysis, semi-structured interviews with members of the Olympiad organizing committees and the application of a questionnaire for data gathering with students. Therefore, it is a qualitative research in the conception of Biklen and Bogdan and Eisner. Thus, the dissertation is structured in four chapters in which I try to present considerations and possibilities about the teaching of history, inserted in the line of research Historical Knowledge in the School Environment. It can be concluded from the research that projects such as ONHB and OCHE, which stimulate scientific investigation by students through their contact with historical sources, promote significant learning and contribute to the dissemination of History in the school environment.